Interpreting Structural Equation Modeling Results: A Reply to Martin and Cullen - Dion, Paul A. (Journal of business ethics, 2008)
This article briefly review the fundamentals of structural equation modeling for readers unfamiliar with the technique then goes on to offer a review of the Martin and Cullen paper. In summary, a number of fit indices reported by the authors reveal that the data do not fit their theoretical model and thus the conclusion of the authors that the model was “promising” are unwarranted.